Schiller und die Philosophische Anthropologie des 20. Jahrhunderts : Ein ideengeschichtlicher Brückenschlag. - Middel, Carina (Quellen und Forschungen zur Literatur- und Kulturgeschichte., 2017)
The series ""QUELLEN UND FORSCHUNGEN ZUR LITERATUR- UND KULTURGESCHICHTE"" (Sources and Research in the History of Literature and Culture), with a rich tradition stretching back to 1874, is an established feature among the renowned publications for German Literary Studies. Edited by Ernst Osterkamp and Werner Röcke at the Humboldt University of Berlin, the series presents examples of high-quality scholarship examining literary texts in conjunction with historical cultural phenomena, particularly with the other arts. There is an explicit demand for literary studies with a transdisciplinary appr